Improving the U.S. Workforce System by Transforming its Performance Measurement System into an Intelligent Information System. - Eberts, Randall W. (Economic Development Quarterly, 2023)
A smart public workforce system requires customized tools to help customers navigate through the complexities of finding a job or finding qualified workers. It also requires that information flow in both directions—from customers to the workforce system and vice versa. This commentary shows some early attempts at constructing algorithms to develop tools and proposes research that is necessary for future refinements. The Workforce Innovation and Opportunity Act (WIOA), the federal program that provides most funds and guidance for the nation's public workforce system, offers some direction for states to follow in constructing various aspects of these tools. The early attempts include a pilot for Georgia, called Frontline Decision Support System (FDSS), and the Value-Added Performance Improvement System (VAPIS) for the state of Michigan. Future research must answer questions such as the efficacy of AI over regression, and how does one go about evaluating such tools.